2018
DOI: 10.3390/mi9070352
|View full text |Cite
|
Sign up to set email alerts
|

Tongue Pressure Sensing Array Integrated with a System-on-Chip Embedded in a Mandibular Advancement Splint

Abstract: Obstructive sleep apnea (OSA), which is caused by obstructions of the upper airway, is a syndrome with rising prevalence. Mandibular advancement splints (MAS) are oral appliances for potential treatment of OSA. This work proposes a highly-sensitive pressure sensing array integrated with a system-on-chip (SoC) embedded in a MAS. The device aims to measure tongue pressure distribution in order to determine the efficacy of the MAS for treating OSA. The flexible sensing array consists of an interdigital electrode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…The tactile perception of the tongue surface is composed of mechanical stimuli received by tens of thousands of tactile corpuscles (Kohyama, 2020; Miles et al, 2018). To explore the actual state of the tactile perception, and further reveal the generation mechanism of the tactile perception of the tongue surface, many researchers try to reproduce the multipoint tactile perception state of the tongue surface using tactile images (Chen et al, 2018; Jiang et al, 2020; Li et al, 2018; Liu et al, 2022; Park et al, 2020, 2021). In this process, they face an arduous task: Using the sensor array with limited acquisition points to obtain the multiple contacts information on the tongue surface (Hori et al, 2009; Liu et al, 2017; Yeh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The tactile perception of the tongue surface is composed of mechanical stimuli received by tens of thousands of tactile corpuscles (Kohyama, 2020; Miles et al, 2018). To explore the actual state of the tactile perception, and further reveal the generation mechanism of the tactile perception of the tongue surface, many researchers try to reproduce the multipoint tactile perception state of the tongue surface using tactile images (Chen et al, 2018; Jiang et al, 2020; Li et al, 2018; Liu et al, 2022; Park et al, 2020, 2021). In this process, they face an arduous task: Using the sensor array with limited acquisition points to obtain the multiple contacts information on the tongue surface (Hori et al, 2009; Liu et al, 2017; Yeh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There are eight research articles and one review article published in this special issue, covering a wide range of topics: implantable sensors for detecting biophysiological and biophysical signals [1,2]; novel transducers for stimulation [3]; miniaturized antennas and biotelemetries for wireless implants [4,5,6] medical electronics and system-on-chip (SoC) [1,7]; and nano/microfabrication technologies for implantable microdevices [2,8,9]. On the device side, Chen et al reported a tongue pressure sensing platform that integrated interdigitated pressure sensing electrodes with SoC on flexible polymer films.…”
mentioning
confidence: 99%